Hubungan Kekuatan Otot Lengan Dengan Kemampuan Servis Atas Pada Atlet Bola Voli di Tingkat Perguruan Tinggi - Deni Rahman Marpaung; Randy Kurniawan; Syakila Putri Halawa; Naila Lulu Qalbi; Zilfityas Dwi Oktiraisya; Triya Panirwati; Fanny Ardila Siregar (JSH: Journal of Sport and Health, 2026)
This study aims to analyze the relationship between arm muscle strength and overhead service ability in volleyball athletes at the university level through a qualitative approach based on previous research and descriptive analysis. The method used is a literature study by reviewing various relevant scientific journals to gain an in-depth understanding of the relationship between the studied variables. Data were collected through the exploration of literature sources discussing arm muscle strength, overhead service techniques, and factors influencing performance in volleyball. The findings indicate that arm muscle strength plays an important role in determining the quality of overhead service, particularly in generating power, maintaining movement stability, and ensuring accuracy of ball direction. In addition, overhead service ability is also influenced by other factors such as coordination, technique, and concentration. The discussion shows that there is a close and interrelated relationship between arm muscle strength and overhead service ability. Therefore, improving arm muscle strength through structured training can contribute positively to enhancing overhead service performance among university-level volleyball athletes.